Faktor penentu Nilai Perusahaan pada Perusahaan Manufaktur sub sektor Makanan dan Minuman - Mario Inigo Radite Kusumo; Temy Setiawan; Theresia Hesti Bwarleling (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The success of a company’s performance can be seen through the value of the company. The higher the value of the company, the investors will be interested in investing. The economic recovery after the pandemic caused people to decide to invest in company shares. The purpose of this study is to provide empirical evidence regarding the effect of corporate social responsibility, managerial gender diversity, managerial nationality diversity and managerial educational background on firm value. This study uses food and beverage sub sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 with a total sample of 55. This research method uses multiple linear regression analysis and uses the SPPSS 26 application. The results of the study state that the variables of corporate social responsibility and managerial gender diversity have a positive effect on firm value. Meanwhile, managerial nationality diversity and managerial educational background diversity have no effect on firm value.